Specular reflectance of anodized 6061-T6 aluminum alloy - Strauss, Jon (Kansas State University, 2012)
This study investigated the specular reflectance properties of 6061-T6 aluminum alloy anodized in accordance with military specification MIL-A-8625 as a function of both etch process time and anodization process potential. Both process parameters affect the specular reflectance characteristics when measured using a 660 nm, collimated diode laser source. The etch process time, when varied between 0.5 to 20 minutes, resulted in a decrease in specular reflectivity with increasing time. The anodization process potential was varied between 10 and 21 volts, with a 15 volt condition producing samples with the greatest specular reflectivity. Between the two parameters, the etch time had the greater effect. Additionally, the dependence of the incident beam angle on specular reflectivity was shown not to have a significant effect when compared to the etch process time and process potential.
Keywords: Aluminum; Specular reflectance; Anodized; Chemical Engineering (0542)